Evaluation of chemical events management following International Health Regulations, 2005: IHR (2005) in provinces located in Special Economic Zone (SEZ) and Border Health Provinces (BHPs) - Namwicha, Satit; Phathong, Jariya; Buranasatitnon, Sutatip (Disease Control Journal, 2022)
Chemical events management was a technical area of Joint External Evaluation (JEE) tool used to prevent, control, and respond to diseases and health hazards in accordance with the International Health Regulations 2005, or IHR (2005). The Department of Disease Control (DDC), Ministry of Public Health (MOPH) has expanded its activities to the provincial level, including the provinces located in the Special Economic Zone (SEZ) and Border Health Provinces (BHPs). This cross-sectional descriptive study aimed to evaluate the implementation of IHR (2005) core capacity in chemical events-related issues, analyze barriers to implementing the program at the provincial level, and provide recommendations for health authorities in SEZ and BHPs. The data were collected by using IHR (2005) JEE tool intended for implementation at the provincial level, of which contents covers technical area 18 - chemical events assessment. This data collection form was developed by DDC for use in 27 provinces. Data were analyzed and interpreted using assessment criteria with descriptive statistics and content analysis. The results found that (1) most of provinces in SEZ and BHPs had no capacity in chemical event management (33.3%), followed by those with demonstrated capacity level (22.2%), moderate capacity level (18.5%), limited capacity level (14.8%), and sustainable capacity level (11.1%). As for the first three activities which were successfully completed, 70.4% of participating provinces have established chemical accident risk database, 66.7% of them have conducted exercise on chemical emergency response at the provincial level, and 66.7% of them have provided a refresher course on the knowledge of chemical events to their respective provincial SRRT team. On the contrary, the first three activities which had yet to be conducted included human resource development plan or training courses related chemical events (51.9% of provinces participating in the study), chemical risk area assessments (48.2%), and integration and standardization of existing Standard Operating Procedures (SOPs) for chemical sampling and delivery for laboratory analysis (44.4%). Additionally, provinces located in the SEZ and BHPs have encountered various operational problems, including an incorrect and incomplete area according to the IHR (2005) – JEE tool, limitations on personnel, resources, and insufficient budget. Therefore, more efforts should be made by the DDC so as to translate the policy into actions with particular emphasis on interagency cooperation, personnel allocation and budget, continued implementation of personnel capacity building program, and monitoring and evaluation (M&E). For provincial level, there should be a clear set of responsibilities, preparations of work plans according to IHR 2005, and cooperation with their local network.